(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A field experiment was conducted at The Agronomy Field, Patuakhali Science and Technology University (PSTU), Patuakhali during the period of May 2013 to August 2013. The experiment was conducted to find out the effect of seed rate on nodulation of dhaincha (Sesbania aculeata) under non-saline agro-ecosystem. The experiment comprised of seven different seed rates viz. 30, 35, 40, 45, 50, 55 and 60 kg ha-1. The experiment was laid out in randomized complete block design with three replications. The seed rates had significant influence on different parameters of dhaincha plant. The maximum plant height was (4.109 m), maximum plant diameter was (0.9200 cm), maximum dry weight of nodule was (5.59 g plant-1) were observed at the seed rate of 30 kg ha-1.In study period the maximum numbers of nodule plant-1 (39.60) at harvest and T7 (60 kg ha-1) showed minimum number of nodules plant-1 (30.33). It was observed that the highest number of abnormal nodules plant -1 (19.87) while (30 kg ha-1) gave the lowest number of abnormal nodules plant -1 (12.47). It was found that the (30 kg ha-1) observed the maximum dry weight of nodules (5.59 g plant-1) and the minimum dry weight of nodules (3.61 g plant-1) was found from (60 kg ha-1). The highest plant population (336.0) was found in T7 (60 kg ha-1) while T1 (30 kg ha-1) showed the lower plant population (114.0). This result indicated that higher seed rate produced the maximum plant population than lower seed rate which ultimately resulted in higher production of biomass. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 309-315